2016
DOI: 10.1002/bit.26019
|View full text |Cite
|
Sign up to set email alerts
|

Acylase‐containing polyurethane coatings with anti‐biofilm activity

Abstract: Due to the prevalence of biofilm-related infections, which are mediated by bacterial quorum sensing, there is a critical need for materials and coatings that resist biofilm formation. We have developed novel anti-biofilm coatings that disrupt quorum sensing in surface-associated bacteria via the immobilization of acylase in polyurethane films. Specifically, acylase from Aspergillus melleus was covalently immobilized in biomedical grade polyurethane coatings via multipoint covalent immobilization. Coatings cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 62 publications
(71 reference statements)
1
29
0
Order By: Relevance
“…The acylase, which was initially found in Variovorax paradoxus and Ralstonia, can block the QS signaling by hydrolyzing the amide bond of AHLs [82][83][84]. The acylase was revealed to decrease the growth of Pseudomonas aeruginosa ATCC 10145 and PAO1 by 60% [85,86] and has been widely applied in human health care; for example, the acylasecoated device showed a well antibacterial property due to the QS signaling disruption by the acylase [87]. The acylase is also chemically immobilized on some nanomaterials to act as an antifouling agent [88].…”
Section: Qs Signals Degradationmentioning
confidence: 99%
“…The acylase, which was initially found in Variovorax paradoxus and Ralstonia, can block the QS signaling by hydrolyzing the amide bond of AHLs [82][83][84]. The acylase was revealed to decrease the growth of Pseudomonas aeruginosa ATCC 10145 and PAO1 by 60% [85,86] and has been widely applied in human health care; for example, the acylasecoated device showed a well antibacterial property due to the QS signaling disruption by the acylase [87]. The acylase is also chemically immobilized on some nanomaterials to act as an antifouling agent [88].…”
Section: Qs Signals Degradationmentioning
confidence: 99%
“…When used as insulation coatings for corrosion, the microbial degradation effect on polyurethane coatings could cause substantial damage, and thus leading to a loss in corrosion resistance. Several investigators have attempted to impregnate antibacterial agents into the matrix of polyurethane coatings to minimize the microbial degradation effect (Stobie et al, 2009;Grover et al, 2016;Yesudass et al, 2017). For example, it was reported that about 0.1-5% of non-toxic antibacterial agents was chemically (rather than physically) incorporated into the polyurethane resins, and thus the antibacterial agents become an integral and permanent part of the molecular structure across the entire polyurethane coating film (Grover et al, 2016).…”
Section: Traditional Polymers Incorporated With Biocides For Biocorromentioning
confidence: 99%
“…Furthermore, the corrosive biodegradation products have been found detrimental to the biofilm-attached metals (Flemming, 1998;Kopteva et al, 2004). To circumvent the problem of microbial degradation, the biocidal functionality has been conferred to the polymer coatings to inhibit the attachment of bacterial cells and subsequent formation in recent years (Crum et al, 1967;Sugama, 1995;Sugama and DuVall, 1996;Thomas et al, 2004;Ananda Kumar et al, 2006;Choi et al, 2007;Yuan et al, 2007Yuan et al, , 2009aYuan et al, ,b,c, 2010aLebrini et al, 2008;Stobie et al, 2009;Videla and Herrera, 2009;Wan et al, 2009;Zafar et al, 2009;Yang et al, 2014;Grover et al, 2016;Yesudass et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…19 Thus, the inactivation of quorum-sensing autoinducers using highly-selective enzyme reactions, called "enzymatic quorum quenching", has been proposed as an effective strategy for the control of biofilm formation. [20][21][22] Three types of auotoinducers have been well documented: cyclic peptides for Gram-positive, N-acyl homoserine lactone (AHL) for Gram-negative, and autoinducer-2 with structure of farnesyl borate dieter for both Gram positive and Gram-negative. [23][24][25] Acylase is one 5 of the well-known quorum quenching enzymes that can degrade the AHL autoinducers by cleaving the acyl amide bond between lactone ring and acyl chain.…”
Section: Introductionmentioning
confidence: 99%